Pengaruh Corporate Governance Terhadap Manajemen Laba Dengan Ukuran Perusahaan Sebagai Variabel Intervening - Utami Puji Lestari; Mudjiyono .; Yetti Iswahyuni (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2023)
Utami Puji Lestari. The Effect of Corporate Governance on Profit Management with Company Size as an Intervening Variable. Semarang Institute of Technology and Business. 16 pages. The data analysis method used is the classical assumption test, hypothesis testing with two-way analysis, and the coefficient of determination. The results showed that the direct effect value was 0.293, and the indirect effect was 0.101 which means that the indirect effect value is smaller than the direct effect. This indicates indirectly that the managerial ownership variable through company size has an insignificant effect on ML. The direct effect value is 0.0.061, and the indirect effect is 0.472 which means that the indirect effect value is smaller than the direct effect. This indicates that institutional ownership through company size has an insignificant effect on earnings management. The direct effect value is 0.16, and the indirect effect is -0.146 which means that the indirect effect value is not greater than the direct effect, this indicates that the Audit Committee indirectly through Company Size has a significant influence on Earnings Management. The direct effect value is 0.324, and the indirect effect is -0.191 which means that the indirect effect value is not greater than the direct effect, this indicates that the Board of Commissioners indirectly through Company Size has a significant influence on Earnings Management.